Research of Rail Application Geometrical Parameter Calculation - LIU Tiejun; LI Jia (机车电传动)
Mathematics principle and algorithm of rail measured data to application geometrical parameter were introduced, and mathematics model equation of geometrical parameter calculation was presented. Test and analysis validated the method with precision. The algorithm was useful to the maintaining for the exiting lines, particularly the longtime operation and deforming ones.